Synthesis of Novel Quin[1, 2-b]Acridines: In Vitro Cytotoxicity and Molecular Docking Studies. (14th September 2021) - Satheeshkumar, Rajendran; Edatt, Lincy; Muthusankar, Aathi; Sameer Kumar, V. B.; Rajendra Prasad, Karnam Jayarampillai
Abstract: An attempted synthesis of 5-aryl-6, 7-dihydrodibenzo[ b, j ][1, 10]phenanthroline derivatives from 2, 3-dihydroacridin-4( 1H )-ones with 2-aminocarboxylic acid derivatives in presence of phosphorus oxychloride at 130˚C yielded a novel class of quin[1, 2- b ]acridine derivatives. The newly synthesized compounds showed a better cytotoxic activity against HeLa and MCF-7 cell lines during the structure–activity relationship (SAR) studies. To discover with the interactions of these molecules, we carried out molecular docking studies using the human protein kinase CK2 inhibitors. The molecular interaction results provided a number of elegant information for the outlook design of more potent inhibitors.